The accumulation of heavy metals in Typha latifolia L. grown in stream carrying secondary effluent - Şaşmaz, Ahmet; Öbek, Erdal; Hasar, Halil (My University, 2008)
Typha latifolia L. fromaquatic plants is widely found throughout Kehli Stream (Elazig, Turkey). This study examined the uptake of some metals by T. latifolia and the transfer from roots to other plant parts. The accumulation of Mn in T. latifolia L. can be suggested as a tolerance strategy due to its transfer factor higher than 1.0. The enrichment coefficients in the leaves of T. latifolia L. were higher than 1.0 for Zn and Mn and often lower than 1.0 for other metals. Similarly, the enrichment coefficients of all metals, except for Cr, in roots of T. latifolia L.were higher than 1.0. This study demonstrated that T. latifolia L. could be considered as either a bio-indicator or a bio-accumulator for sediments and water polluted by metals.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Heavy metal uptake; Bioaccumulation; Contaminated sediment; Typha latifolia